Observation On The Reduction Of Iron Oxide By Graphite And Coke - Mohd Azrisyazwan Bin Zainuddin (School of Metallurgy Engineering, University Malaysia Perlis, 2016)
This present study is to investigate the reduction of iron oxide with metallurgical coke and graphite used in this project. The purpose of this study mainly was to investigate the possibilities of reducing hematite to metallic iron. The iron oxide with graphite and coke reduction occurred in stepwise of hematite (Fe2O3) to magnetite (Fe3O4), and to metallic iron (Fe) respectively. The reducing agent, metallurgical coke and graphite play a major role in reduction behavior study. Three different proportions were undergoes reduction process in horizontal tube furnace with nitrogen gas flow at high temperature (950C) reactions with difference soaking time of 60 minutes, 120 minutes and 180 minutes. The reduction were determined by X-ray Diffraction (XRD) analyzed, X-ray Diffraction (XRF) analyzed with Scanning Electron Microscope and Energy dispersive spectrometry (SEM/EDS). The iron oxide were founded in XRD and EDS pattern.. XRD pattern detected hematite peaks at before reduction changes to magnetite after reduction were done. Thus, based on result presented by XRD, SEM and EDS analysis the reducing percentage of iron oxide with graphite and coke; reduction performance were improved as well.